Clinical evaluation of TIVA by romifidine as a premedication, midazolam and ketamine in donkeys: Ayad A. Amin, Abed F. Ali1, E’atelaf A .Al-Mutheffer - Amin, Ayad A. (The Iraqi Journal of Veterinary Medicine, 2012)
The objective of this study was to determine the clinical effects of total intravenous anesthesia (TIVA) by romifidine 0.1mg/kg as a premedication and anesthesia by intravenous injection of a mixture of midazolam 0.1 mg/kg and ketamine hydrochloride 2.2 mg/kg in the ten health She donkeys. The maintenance of anesthesia was performed by intravenous infusion of a mixture of the midazolam 0.065mg/kg/hrs and ketamine 6.6mg/kg /hrs prepared in 500ml normal saline. Data were collected just before intravenous administration of premedication (control data) and after the administration of anesthetics drugs at 5, 10, 15, 20, 25, 30, 45, 60 and 90 minutes. The clinical parameters measured included: Anesthetic Parameter (induction, anesthetic time and recovery), rectal body temperature, arterial oxyheamglobin saturation in blood (SPO2), analgesia, muscles relaxation, at the above times until the donkey responds to external stimuli. The results of the induction and maintenance of general anesthesia by this regime was found to be superior and stable. Recovery from anaesthesia was smooth and similar quality in all animals. The body temperature showed significant differences between control and 5min 37.35 ± 0.054 ;37.19 ± 0.08 ◦C with 15 min and above to the 60 min, while in SPO2 (%) the result showed significant difference (P<0.05) in time 90 min 97.4 ± 0.541 with 10min ; 15min 94.6 ± 1.229 ;93.7 ± 1.075 %and 20 min 93.9 ± 1.075%. There were no adverse effects noted following this anesthetic regime.